Pendampingan Pastoral Orang Tua dalam Pengaruh Penggunaan Gadget dan Pertumbuhan Rohani terhadap Anak Usia Dini pada Masa Pandemi - Baran Rante Payung; Alpribet Rerung (Departement of Mathematics Education, 2023)
Gadgets are very influential in human life, it can even be said that gadgets are able to seize various things from human life so that many people make mistakes in using these gadgets, especially in early childhood during this pandemic. Where gadgets are supposed to be used for school purposes but in fact many young children do not use them according to their needs. The purpose of this study is to find out how parents provide pastoral assistance to early childhood in using gadgets and for children's spiritual growth so that children do not get carried away in addiction to playing gadgets and even damage children's brain, senses and mentality. The method used in this research is a qualitative method in order to help provide enlightenment and understanding to be able to understand the purpose of this paper. Gadgets can be seen from the negative and positive side and it is believed that from the positive side it can make humans to access and know various things but if viewed from the negative side it will damage humans, especially children and make children more inclined to be lazy. This is where parental pastoral assistance is needed in supervising and monitoring children in the use of gadgets so that they are not excessive. Then have a commitment and be consistent with the child so that the child does not continue to spend time only playing gadgets. Therefore, the role of parents is very important to provide understanding and enlightenment to children about the impact of playing gadgets in the long term so that children can realize the dangers of gadgets. Presumably through this article, we can all know how to use gadgets.